2017
DOI: 10.1155/2017/5164292
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of the Dipeptidyl Peptidase-4 Inhibitor Sitagliptin: A Review in Type 2 Diabetes

Abstract: Diabetic nephropathy (DN) is now the single commonest cause of end-stage renal disease (ESRD) worldwide and one of the main causes of death in diabetic patients. It is also acknowledged as an independent risk factor for cardiovascular disease (CVD). Since sitagliptin was approved, many studies have been carried out revealing its ability to not only improve metabolic control but also ameliorate dysfunction in various diabetes-targeted organs, especially the kidney, due to putative underlying cytoprotective prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 190 publications
(200 reference statements)
3
28
2
Order By: Relevance
“…Among a variety of potential mechanisms by which DPP4 inhibitors exert this renoprotective effect on damaged kidneys, we focused on the regulation of NLRP3 inflammasome activity. Similarly to previous studies [29,33], we found no improvement in serum creatinine levels by DPP4 inhibition. Proteinuria contributes to tubulointerstitial inflammation, leading to renal fibrosis.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Among a variety of potential mechanisms by which DPP4 inhibitors exert this renoprotective effect on damaged kidneys, we focused on the regulation of NLRP3 inflammasome activity. Similarly to previous studies [29,33], we found no improvement in serum creatinine levels by DPP4 inhibition. Proteinuria contributes to tubulointerstitial inflammation, leading to renal fibrosis.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, we showed that these inflammatory processes were effectively blocked by sitagliptin treatment. Previous studies have shown that sitagliptin treatment reduces renal inflammation and oxidative stress in animal models of type 2 diabetes [29,35].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given that the DPP4 enzyme is present in various components of the endothelial and epithelial kidney tissues (including renal proximal tubular epithelia, podocytes, mesangial cells, and pre-glomerular vascular smooth muscle cells), it has been hypothesized that DPP4 inhibitors will have a protective effect on the kidney by reducing inflammation and fibrosis and improving overall function 6,7 . However, other mechanisms may be responsible for acute changes in renal function including fluid depletion and volume contraction via vomiting and diarrhea, although evidence exists suggesting a beneficial effect of natriuretic and diuretic properties of DPP4 inhibitors 8,9 . Findings from observational studies have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%